1967
DOI: 10.1128/jb.94.5.1411-1416.1967
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Biological Properties of Sonically Treated Vi Antigen

Abstract: Electrophoretically purified Vi antigen from Citrobacter freundii 5396/38 was depolymerized by sonic treatment. The treatment caused an 80% reduction in specific viscosity and a reduction in molecular weight from 1.6 x 106 to 3.9 X 104. The 0-acetyl and N-acetyl contents of the antigen and its infrared spectrum remained unchanged. The sonically treated antigen was only 1 % as effective as the original antigen in eliciting protection in mice against challenge with Salmonella typhi. Sonically treated antigen als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…These ¢ndings suggested that the F1 antigen in the killed whole cell vaccine had been denatured [11] and the breakdown of F1-antigen in this vaccine has been reported [22]. These ¢ndings are similar to those reported for the Vi capsular antigen of Salmonella typhi, where high molecular weight forms are reported to induce better protection than low molecular weight forms of the antigen [23].…”
Section: Discussionsupporting
confidence: 75%
“…These ¢ndings suggested that the F1 antigen in the killed whole cell vaccine had been denatured [11] and the breakdown of F1-antigen in this vaccine has been reported [22]. These ¢ndings are similar to those reported for the Vi capsular antigen of Salmonella typhi, where high molecular weight forms are reported to induce better protection than low molecular weight forms of the antigen [23].…”
Section: Discussionsupporting
confidence: 75%
“…In fact, analysis of plague vaccine-derived F1 by analytical gel filtration chromatography in our laboratory indicated that the bulk of the antigen existed in lower-molecular-mass aggregates, with the larger aggregate representing only a minor species (2). This finding is interesting in light of the fact that protective immunogenicity of other bacterial antigens, such as Vi antigen of Salmonella species, is a function of molecular mass (25). Alternatively, differences in the protective immunogenicity of the plague vaccine may be simply due to the absence of any added adjuvant.…”
Section: Discussionmentioning
confidence: 96%
“…Since vaccines will be stored at c3 to 80C, the stability characteristics of OAcPec and Vi can be considered similar. Although they are antigenically indistinguishable, OAcPec, unlike Vi, is not immunogenic in mice, probably because of its lower molecular weight (17). In mice, OAcPec and Vi protein conjugates elicited comparable levels antibodies: reinjection of both conjugates induced a statistically significant rise of antibodies (booster effect).…”
Section: Discussionmentioning
confidence: 99%
“…pectin is easy to obtain, and its purification is simpler than extraction of Vi from S. typhi; (ii) pectin can be measured during the synthesis of the conjugate and in the final container by a colorimetric reaction; (iii) there is no solubility problem, and the yield of OAcPec conjugates is higher than with Vi; and (iv) at 4°C, the storage temperature of vaccines, the stability of OAcPec is similar to that of Vi. The one deficiency of OAcPec that we are aware of is its lower Mr. As with other polysaccharides, the molecular weight of the Vi alone and as a conjugate is related to its immunogenicity (17,18,24). For these reasons, we plan a clinical trial to compare the immunogenicities of our OAcPec and Vi conjugates.…”
Section: Downloaded Frommentioning
confidence: 99%